Protein-protein Docking Studies of Estrogen Receptor Alpha and TRIM56 Interaction for Breast Cancer Drug Screening - Dhiani, Binar Asrining; Nurulita, Nunuk Aries; Fitriyani, Fitriyani (Indonesian Journal of Cancer Chemoprevention, 2022)
Breast cancer is the highest mortality cause in women with cancer. Protein-protein docking for target-based screening is an effective approach in breast cancer drug discovery via estrogen receptor (ER) signaling. TRIM56, an E3 ubiquitin protein ligase, can bind to and stabilize ER alpha. Thus, drug screening that can inhibit or weaken the interaction between ER alpha and TRIM56 is promising to obtain novel yet specific breast cancer drugs. In this study, we performed protein-protein docking studies for ER alpha and TRIM56 interaction and virtual screening for FDA-approved drugs from the ZINC database against ER alpha and TRIM56 complex protein model structure. We utilized Cluspro 2.0, PyRx 0.8, and Pymol 2.4.1 to conduct protein-protein docking, virtual screening, and model structure visualization. PIP and PLIP software were also applied to analyze the amino acid residue between proteins or protein-ligands. Based on the protein-protein docking, ER alpha and TRIM56 established interaction. Utilizing this complex protein as a macromolecule in the virtual screen of 1071 molecules of FDA-approved drugs, we obtain the top five lowest binding energy molecules i.e., dutasteride, dihydroergotamine, nilotinib, ergotamine, and bromocriptine. In addition, the energy binding affinity between ER alpha-dutasteride complex with TRIM56 was weakened in the presence of dutasteride. In conclusion, protein-protein docking between ER alpha-TRIM56 was able to select FDA-approved drugs that could bind to the complex, and dutasteride binding to ER alpha-TRIM56 complex weakened the interaction.Keywords: protein-protein docking, estrogen receptor alpha, TRIM56, breast cancer, ubiquitin.